2014
DOI: 10.1371/journal.pone.0115847
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neutrophil Activation Markers as Novel Surrogate Markers of CF Lung Disease

Abstract: Background and aimsCystic Fibrosis (CF) lung disease is characterized by progressively declining lung function and represents a major factor contributing to the high morbidity and mortality associated with CF. However, apart from spirometry, respiratory disease surrogate markers reliably indicating CF lung disease and the occurrence of pulmonary exacerbations (PEx) are still lacking. Within this study, we aimed to identify new experimental biomarkers for the detection of CF lung disease.Methods54 adult and 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Our studies extend the limited available observations that have already been published on examining HA pathobiology in the progression of CF airway disease or as a marker of clinical exacerbation (17). In fact, HA serum levels have not been found to be impacted by advanced lung disease in pediatric and adult patients with CF (28). Locally in the lung, HA at one time was reported to be the only detectable GAG in CF (29), although other sugars have been subsequently identified, which may also play an important role in CF pathophysiology (30).…”
Section: Discussionsupporting
confidence: 71%
“…Our studies extend the limited available observations that have already been published on examining HA pathobiology in the progression of CF airway disease or as a marker of clinical exacerbation (17). In fact, HA serum levels have not been found to be impacted by advanced lung disease in pediatric and adult patients with CF (28). Locally in the lung, HA at one time was reported to be the only detectable GAG in CF (29), although other sugars have been subsequently identified, which may also play an important role in CF pathophysiology (30).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, each patient received regular haematological and biochemical investigation as well as a pulmonary function test (FEV1, VC) [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study of adults and children with moderate-to-severe CF lung disease reported elevated serum MMP-8, MMP-9, and TIMP-1 levels in clinically stable CF patients, and higher serum MMP-8 and MMP-9 levels in adult CF patients having acute pulmonary exacerbations. 53 However, serum MMP-8, MMP-9, and TIMP-1 levels were not correlated with CF liver disease or pancreatic insufficiency in this cohort.…”
Section: Mmp Levels In Cf Blood Samplesmentioning
confidence: 55%